2021
DOI: 10.3390/ijms22084090
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Reconsolidation of Licit Drug Memories to Prevent Relapse: Focus on Alcohol and Nicotine

Abstract: Alcohol and nicotine are widely abused legal substances worldwide. Relapse to alcohol or tobacco seeking and consumption after abstinence is a major clinical challenge, and is often evoked by cue-induced craving. Therefore, disruption of the memory for the cue–drug association is expected to suppress relapse. Memories have been postulated to become labile shortly after their retrieval, during a “memory reconsolidation” process. Interference with the reconsolidation of drug-associated memories has been suggeste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 110 publications
1
7
0
Order By: Relevance
“…Thus, memories have been suggested to be reactivated upon their retrieval, leading to a process of a temporary destabilization followed by restabilization, termed reconsolidation [7][8][9] . Indeed, recent studies in animal models and humans have shown that pharmacological and behavioral interventions during reconsolidation immediately following memory retrieval can attenuate relapse to alcohol drinking and seeking [3][4][5][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, memories have been suggested to be reactivated upon their retrieval, leading to a process of a temporary destabilization followed by restabilization, termed reconsolidation [7][8][9] . Indeed, recent studies in animal models and humans have shown that pharmacological and behavioral interventions during reconsolidation immediately following memory retrieval can attenuate relapse to alcohol drinking and seeking [3][4][5][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Relapse is often caused by cue-induced craving, where an alcohol-associated cue evokes strong craving and relapse even after protracted abstinence. Therefore, disruption of the memory for the cue-alcohol association is expected to reduce or even prevent relapse [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…A promising approach for the disruption of maladaptive memories is to target the process of memory reconsolidation 10,13,14 . Thus, it is believed that reactivation of stable memories via their retrieval initiates a 5-6-hour window, during which the memories become flexible and labile, before their re-stabilization, in the process of “memory reconsolidation” 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to environmental cues or contexts associated with drug elicits craving and relapse, which is the core primary clinical problem in drug addicts (Childress et al, 1999 ; Crombag et al, 2008 ; Chen et al, 2021b ). To address the persistent propensity for relapse, an increasing number of studies suggest that disrupting drug-associated memory, which maintains conditioned reinforcing properties through various manipulations, is a promising strategy to prevent relapse (Milton and Everitt, 2010 ; Jian et al, 2014 ; Barak and Goltseker, 2021 ).…”
Section: Introductionmentioning
confidence: 99%